Denitrifier communities impacted by heavy metal contamination in freshwater sediment. (November 2018) - Guo, Qingwei; Li, Ningning; Bing, Yongxin; Chen, Sili; Zhang, Zhengke; Chang, Sha; Chen, Yao; Xie, Shuguang
Abstract: Heavy metals are widely detected in natural environments, however their impacts on denitrifier community in freshwater ecosystem remain unclear. The present study investigated the changes of denitrifier communities (based on nosZ (nitrous oxide reductase) gene) in a freshwater reservoir contaminated by a severe accidental spill of heavy metals. The abundance of nosZ -denitrifiers drastically decreased, and their community richness, diversity and structure also showed considerable variations. The mainly detected denitrifying bacteria included Pseudogulbenkiania, Pseudomonas and two unknown groups. These major nosZ -denitrifier groups responded in different ways to heavy metal pollution. Metal contamination could exert a profound influence on denitrifier community in freshwater sediment. This work could provide some new insights to the impact of metal pollution on nitrogen cycling. Graphical abstract: Image 1 Highlights: Heavy metal impact on freshwater sediment denitrifier community was investigated. Metal pollution affected denitrifier abundance, diversity and community structure. Pseudogulbenkiania and Pseudomonas could be adapted to heavy metal pollution. Abstract : This work provides the first evidence that heavy metal contamination had a profound influence on denitrifier community in freshwater sediment.